2018
DOI: 10.1038/s12276-018-0162-6
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase TRIM25 regulates adipocyte differentiation via proteasome-mediated degradation of PPARγ

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a ligand-dependent transcription factor that regulates adipocyte differentiation and glucose homeostasis. The transcriptional activity of PPARγ is regulated not only by ligands but also by post-translational modifications (PTMs). In this study, we demonstrate that a novel E3 ligase of PPARγ, tripartite motif-containing 25 (TRIM25), directly induced the ubiquitination of PPARγ, leading to its proteasome-dependent degradation. During adipocyte different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…To our knowledge, C 7 is the only key residue on the domain that has not been individually mutated for this purpose. However, it has been shown that simultaneous mutations on either C 1 +C 7 or C 6 +C 7 abolish the ligase activity of AMFR and some TRIM family members, respectively (Wang et al, 2014;Liu et al, 2017a;Lee et al, 2018a). As shown in Figure 3, many E3 ligases have been inactivated by simultaneous mutations on C 1 +C 2 .…”
Section: Inactivating Ring-type E3s By Mutating the Zinc-coordinatingmentioning
confidence: 99%
“…To our knowledge, C 7 is the only key residue on the domain that has not been individually mutated for this purpose. However, it has been shown that simultaneous mutations on either C 1 +C 7 or C 6 +C 7 abolish the ligase activity of AMFR and some TRIM family members, respectively (Wang et al, 2014;Liu et al, 2017a;Lee et al, 2018a). As shown in Figure 3, many E3 ligases have been inactivated by simultaneous mutations on C 1 +C 2 .…”
Section: Inactivating Ring-type E3s By Mutating the Zinc-coordinatingmentioning
confidence: 99%
“…TRIM25 is a RNA-binding protein and belongs to the Tripartite Motif (TRIM) family of E3 ubiquitin ligases, which catalyzes the addition of polyubiquitin chains to its substrates for degradation [30][31][32][33] . We performed co-immunoprecipitation (Co-IP) analysis and results showed TRIM25 bound with all three IGF2BPs ( Fig.…”
Section: Trim25 Is the E3 Ligase That Mediates Igf2bps Ubiquitinationmentioning
confidence: 99%
“…TRIM25 possesses E3 ligase activity (Zang et al, 2017; Lee et al, 2018; Li et al, 2018). TRIM25 expression levels affected the protein expression of PTEN.…”
Section: Resultsmentioning
confidence: 99%
“…TRIM25 acted on AKT signaling to modulate the resistance of HCC cells to EPI. Lastly, TRIM25 was an ubiquitin E3 ligase for PPARγ and metastasis‐associated 1 protein (Zang et al, 2017; Lee et al, 2018; Li et al, 2018). In the current study, we demonstrated that TRIM25 bound to PTEN and TRIM25 knockdown inhibited PTEN ubiquitination (Figure 5), and suggested a potential regulatory mechanism of TRIM25 on PTEN/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%